(untitled) (Annals of Medical Research, 2021)
Aim: To determine the relationship between footwear fit and foot deformities, musculoskeletal disorders, and physical activity level.Material and Methods: One hundred physically healthy individuals were included in the study. Footwear fit was examined via the footwear assessment score, foot deformities were examined via the Total Foot Deformity Scoring and musculoskeletal disorders were evaluated with Cornell Musculoskeletal Discomfort Questionnaire. The physical activity level of the individuals was measured by the International Physical Activity Questionnaire. Spearman correlation coefficient was used to determine the relationship between variables.Results: No statistically significant relationship was found between footwear fit and right foot deformity scores (p> 0.05). However, there was a weak negative correlation between the participants’ footwear fit and left foot pes planus (r = -0.242, p = 0.015), pes cavus (r = -0.245, p = 0.014), and total deformity scores (r = -0.208, p = 0.038). There was no statistically significant relationship between footwear fit and musculoskeletal disorders and physical activity levels (p> 0.05).Conclusion: There was no relationship between footwear fit and musculoskeletal pain and physical activity level in the study population. However, it was found that proper footwear use was associated with foot deformities. It is considered that the present study can be used in the future as a reference in studies conducted with populations with certain pathologies.